2010
DOI: 10.2147/oajsm.s10623
|View full text |Cite
|
Sign up to set email alerts
|

Pace bowlers in cricket with history of lumbar stress fracture have increased risk of lower limb muscle strains, particularly calf strains

Abstract: Objective: To assess whether a history of lumbar stress fracture in pace bowlers in cricket is a risk factor for lower limb muscle strains. Methods: This was a prospective cohort risk factor study, conducted using injury data from contracted first class pace bowlers in Australia during seasons 1998-1999 to 2008-2009 inclusive. There were 205 pace bowlers, 33 of whom suffered a lumbar stress fracture when playing first class cricket. Risk ratios ([RR] with 95% confidence intervals [CI]) were calculated to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…A previous history of lumbar stress fracture in cricket fast bowlers was associated with a 1.5 times increase in hamstring injury risk,51 while any severe back injury sustained by an elite or subelite Australian football player was associated with subsequent hamstring injury by more than a twofold 30. Cricket fast bowlers with a previous history of lumbar stress fracture were also found to have a fourfold increased risk of sustaining a calf injury and a twofold risk of sustaining a subsequent quadriceps injury 51. The same study did not find any significant association between lumbar stress fractures and groin or ankle sprains and joint injuries.…”
Section: Discussionmentioning
confidence: 97%
“…A previous history of lumbar stress fracture in cricket fast bowlers was associated with a 1.5 times increase in hamstring injury risk,51 while any severe back injury sustained by an elite or subelite Australian football player was associated with subsequent hamstring injury by more than a twofold 30. Cricket fast bowlers with a previous history of lumbar stress fracture were also found to have a fourfold increased risk of sustaining a calf injury and a twofold risk of sustaining a subsequent quadriceps injury 51. The same study did not find any significant association between lumbar stress fractures and groin or ankle sprains and joint injuries.…”
Section: Discussionmentioning
confidence: 97%
“…Such research is usually not undertaken in the context of injury surveillance but, fortuitously, the cohort design prescribed by the consensus statement16–19 and adopted for the New Zealand cricket injury surveillance system lends itself to the investigation of risk factors 34. Orchard et al have already demonstrated the utility of this design in identifying risk factors for bowling injury 3 32 38. If bowling and batting exposure data were added to the New Zealand surveillance system then the potential would exist to investigate risk factors for bowling in elite New Zealand cricketers.…”
Section: Discussionmentioning
confidence: 99%
“…15,23,27,32,42,43,46 While the incidence of injuries is more or less the same, the prevalence of injuries has been steadily increasing because of the increasing number of matches played and the decreasing amount of rest periods between matches. 30 The most common cricket injury reported is hamstring strain, and most severe is lumbar stress fracture in young fast bowlers, which is usually season ending. 30,34 Bowling (41.3%), fielding, and wicket keeping (28.6%) account for most injuries.…”
Section: Epidemiologymentioning
confidence: 99%
“…30 The most common cricket injury reported is hamstring strain, and most severe is lumbar stress fracture in young fast bowlers, which is usually season ending. 30,34 Bowling (41.3%), fielding, and wicket keeping (28.6%) account for most injuries. 43 Acute injuries are most common (64%-76%), with the rest being acute-on-chronic (16%-22.8%) and chronic (8%-22%).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation